Analysis Of Attack Velocity and Accuracy in Banjarbaru City Fencing Athletes - Norhalizatul Isnaniah; Herita Warni; Mita Erliana (Indonesian Journal of Physical Education and Sport Science)
Studi purpose. The purpose of this study is to determine the Speed and Accuracy of Attacks on Fencing Athletes when making attacks lacking speed and accuracy so as to make attack techniques not optimal and effective which have an impact on points and endurance.